Development of Competitive Indirect Enzyme-linked Immunosorbent Assay for Detection of Cephalexin Residues in Milk - Sharma, Rajan (Indian Journal of Dairy Science, 2017)
In this study a rapid competitive enzyme-linked immunosorbent assay (ELISA) was developed for the detection of cephalexin (CFX) residues in milk. A simple strategy for the production of haptens for CFX was demonstrated with Keyhole limpet hemocyanin. This hapten conjugate was used as immunogen to successfully raise the polyclonal antibodies against CFX. Utilizing these antibodies, an ELISA was developed to screen CFX residues in milk. The detection limit was calculated as 10 ppb in milk, which was lower than the European Union prescribed Maximum Residue Limit of 100 ppb in milk. Recovery of CFX from spiked milk sample was quantitative. The method can be used for rapid screening of milk samples for CFX residues.Â